Prevalência de asma e sensibilização alérgica em crianças e adolescentes com doença falciforme - Angel, Andrea [UNIFESP] (2017)
Objectives: To identify the prevalence and association of asthma, allergic sensitization and altered pulmonary function among patients with sickle cell disease versus controls without sickle cell disease. Methods: A unicentric and transversal study where the participants (patients and controls) aged 6 to 18 years answered the questionnaire of the International Study of Asthma and Allergies in Childhood (ISAAC), complemented with anamnesis directed towards the associated clinical outcomes. All patients underwent immediate hypersensitivity skin tests with aeroallergens and pulmonary function evaluation (spirometry). Regarding the statistical analysis, parametric and non-parametric methods were used depending on the variables studied. Tests were considered significant when p <0.05. Results: Eighty-eight patients were compared with 44 controls, who did not differ in age, weight, height and body mass index. The prevalence of asthma was 13.6% in the group of patients compared to 15.9% in the control group (p> 0.05). Allergic sensitization was observed in 45.5% of the patients and in 31.8% of the control group (p> 0.05), being more frequent for mites in both groups, with 56.8% in the group of patients and 59,3% in the control group. Sensitization to two or more allergens occurred in 29.5% of the patients, and in 20.5% of the control group (p> 0.05). Pulmonary function was abnormal in 33.8% of the patients and in 10.8% of the control group (p <0.05). The obstructive pattern occurred in 26.8% of the patients and in 5.4% of the controls, and the restrictive in 10.8%, and 5.4% respectively. The diagnosis of asthma was not associated with atopy in any of the groups. Asthma, wheezing and wheezing in the last 12 months had a significant association in patients with obstructive pulmonary function (p <0.001, p=0,020 and p=0.026, respectively). Conclusions: The occurrence of asthma, allergic sensitization and alteration in pulmonar function in patients with sickle cell disease reinforces the importance of routine monitoring of these diagnoses, allowing early treatment and preventing the evolution of pulmonary disease in adulthood.